Nature, meaning and content management Total Quality (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The study of the Total Quality Management (TQM) has been analyzed under different perspectives generating numerous definitions. Nowadays, a theoretical framework generally accepted does not exist. Thus, the present paper has the aim to deep on this and it summarizes the main contributions that appear in the specialized literature in order to define what is the TQM. So, we present the principles and thecritical factors for operation of TQM.
Keywords: Total Quality Management (TQM); Principles; Factors.